2015
DOI: 10.1021/acscatal.5b00969
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Transfer Hydrogenation of Nitroarenes Catalyzed by Highly Dispersed, Supported Nickel Nanoparticles

Abstract: A recyclable highly dispersed Ni/SiO 2 catalyst was prepared by atomic layer deposition. Chemoselective reduction of nitroarenes was studied using the prepared Ni/SiO 2 as the catalyst and hydrazine hydrate as a hydrogen donor. Different kinds of nitroarenes were converted to the corresponding anilines with high yields. The high activity of the catalysts could be a result of the highly dispersed Ni nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 33 publications
1
88
0
Order By: Relevance
“…Nitroarenes with nonreducible groups such as -CH 3 , -OH, -NH 2 , and -CF 3 ( Table 3, entries 1-9), were quantitatively transformed into the corresponding amines in yields >99 %. Furthermore, we were pleased to find that halo (F, Cl, Br)-substituted nitroarenes could be reduced to the corresponding anilines with no discernible dehalogenation ( Table 3, entries [10][11][12][13][14][15][16][17][18][19][20]. A number of other reducible functional groups (e.g., carboxy, ester, nitrile, amide, and sulfanilamide) were tolerated in the reduction reaction ( Table 3, entries [21][22][23][24].…”
Section: Catalytic Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitroarenes with nonreducible groups such as -CH 3 , -OH, -NH 2 , and -CF 3 ( Table 3, entries 1-9), were quantitatively transformed into the corresponding amines in yields >99 %. Furthermore, we were pleased to find that halo (F, Cl, Br)-substituted nitroarenes could be reduced to the corresponding anilines with no discernible dehalogenation ( Table 3, entries [10][11][12][13][14][15][16][17][18][19][20]. A number of other reducible functional groups (e.g., carboxy, ester, nitrile, amide, and sulfanilamide) were tolerated in the reduction reaction ( Table 3, entries [21][22][23][24].…”
Section: Catalytic Reactionmentioning
confidence: 99%
“…Functionalized aromatic amines are important intermediates in the production of a range of pharmaceuticals, agrochemicals, cosmetics, herbicides, dyes, and polymers Amines can be obtained through the catalytic hydrogenation of the corresponding aromatic nitro compounds by using reducing agents such as hydrosilanes, sodium borohydride, hydrazine derivatives,, formic acid, and molecular hydrogen , . However, selectivity in the targeted reduction of the –NO 2 group in the presence of other reactive function groups (e.g., alkenes, nitriles, esters, and halogen groups) remains a big challenge for the production of aromatic amines . Homogeneous metal catalysts, especially Ru and Ir complexes, are usually used for the catalytic hydrogenation of nitro compounds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Hollow carbon nanospheres are special materials and have attracted much attention in catalysis, drug delivery carriers because of their outstanding properties such as option for easy surface functionalisation, shell permeability, low density, cheap and bio-compatiblilty. [6][7][8][9][10][11] Moreover, porous hollow carbon nanospheres (HCNSs) found to firmly retain catalytic centre's and facilitate recycling of catalysts without any significant loss of activity or selectivity and hence entrapping nanocrystals at porous HCNSs is highly preferred. [12] It has been demonstrated that surface structure and electronic state dictate the activities of Pt-based material.…”
mentioning
confidence: 99%
“…[15] PtPd/AuPd/AuPtmixed metal oxide, [16] g-Fe 2 O 3 /C, [17] Ni/Al 2 O 3 -Pt/TiO 2[18] and oxygen-implanted MoS 2 catalyst. The prepared materialw as wellc haracterized by XRD, HR-TEM, BET surfacea rea,E DX and XPS analyses.…”
mentioning
confidence: 99%